Given the expression:
![27=45+9a](https://img.qammunity.org/2023/formulas/mathematics/college/8fwrr5wia4iq3ioau2cczjhewfo25qgxw1.png)
to solve for a, we have to move every term and coefficient to the other side. First we move the 45 to the other side with a negative sign (since it is adding to 9a) and then we move the 9 to the other side dividing, since it is multiplying a. Then we get the following:
![\begin{gathered} 27=45+9a \\ \Rightarrow27─45=9a \\ \Rightarrow9a=─18 \\ \Rightarrow a=(─18)/(9)=─2 \\ a=─2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5wbyzl5q3bb43g92owubrhal2c2y943oua.png)
therefore, a=-2